MUSIK SEBAGAI SARANA PENGUATAN KARAKTER SOSIAL ANAK USIA DINI - Winarti, Winarti; Tika, Rahma (Ensiklopedia of Journal, 2025)
Abstract: Music plays a vital role in the development of children’s social and emotional skills, especially in early childhood education. This article aims to explain the significance of music as a medium for strengthening social character, such as empathy, cooperation, discipline, and self-confidence. The research applies a qualitative descriptive approach through literature reviews and observation of music-based learning practices in early childhood education institutions. The results indicate that music activities, including singing, rhythmic games, and group performances, are effective in helping children internalize positive values and patterns of social interaction. Moreover, music supports children’s holistic development by combining cognitive, emotional, and social aspects in an enjoyable learning experience. This study concludes that integrating music into early childhood education can be an effective pedagogical strategy for character building, which provides implications for teachers, parents, and policymakers.Keywords: early childhood education; music learning; social character; empathy; cooperation.